Apurinic/apyrimidinic (AP) endonuclease from Dictyostelium discoideum: cloning, nucleotide sequence and induction by sublethal levels of DNA damaging agents. - Freeland, T M (1996)
We have cloned an AP endonuclease gene (APEA) from Dictyostelium discoideum, along with 1.8 kb of the 5' flanking region. There are no introns. The sequence predicts a protein of 361 amino acids, showing high homology to the major human/Escherichia coli exonuclease III family of AP endonucleases. There is 47% identity and 64% similarity to the Ape endonuclease of human cells using the C-terminal 257 amino acids of the Dictyostelium protein. The 104 amino acids on the N-terminus show only low homology with other AP endonucleases. Instead, this region shows high homology with the acid-rich regions of proteins associated with chromatin, such as nucleolins and HMG proteins. The gene is transcriptionally activated up to 7-fold after treatment of cells with sublethal levels of DNA damaging agents, including ultraviolet light, MNNG and bleomycin. Induction does not occur following blocking of replication fork polymerases with aphidicolin. It is not eliminated by treatment with kinase or phosphatase inhibitors. Four DNA damage-sensitive mutants all retained the DNA damage-induced up-regulation.